Diversity of parasites and microorganisms of Caspian cereal fish - E. A. Voronina; V. V. Volodina; S. A. Dyakova; A. V. Konkova (Российский паразитологический журнал, 2019)
The aim of the study was to investigate a species composition of parasites and microorganisms and determine infection rate of Caspian herrings. Methods and materials. The objects of the study were Caspian and big-eyed shad, Alosa braschnikowi, that were caught at the aquatic area of the Northern Caspian Sea in spring period 2014, 2015. Collection and processing material was carried out in accordance with generally accepted methods in parasitology and microbiology. Scientists used determinants in species identification. Results and discussion. Parasitophauna of Alosa braschnikowi, Caspian and big-eyed shads were presented by 7 species, relative to classes: Monogenoidea - 1; Crustacea - 1; Trematoda - 2; Nematoda - 2; Acanthocephala - 1. Wide-ranging enteral trematodes Pseudopentagramma symmetricum induce high level of infection of herrings. Fauna is the most variously presented by Caspian big-eyed shads. Fluctuations in parasitophauna structure are connected with ecological conditions, food chains and specificity of parasites to theirs hosts. Indicators of transformation processes of ecosystems are indicator species of parasites and fish microorganisms. As a part of the study it is estimated, that internal organs and gills of herrings were contaminated by microorganisms. The maximum number of bacterium was noted in intestines and gills. The Enterobacteriaceae microorganisms held the dominant position. Besides bacterium there are have been revealed cystophores of micromycetes in liver and spleen in the process of organs microscopic examination. All revealed parasites and microorganisms were characterized by epizootic and epidemiologic significance. However they coexist on the level of symptom-free carriage, without exhibiting the development of invasive and infectious processes in the body of the examined fishes.